Primary dysmenorrhea in adolescents: Association with attention deficit hyperactivity disorder and psychological symptoms - Cihan Kabukçu; Bürge Kabukçu Başay; Ömer Başay (Elsevier, 2021)
Objective: No prior study has investigated the relation of primary dysmenorrhea (PD) with attention deficit hyperactivity disorder (ADHD) symptoms in adolescent age groups. This study aimed to investigate the relationship of PD with ADHD and psychological symptoms among adolescents. Another objective was to examine the PD related non-psychogenic factors and sleep quality. Materials and methods: Two hundred nine adolescent girls who applied to policlinics for various reasons were enrolled. All participants completed self-report questionnaires. Questionnaire for sociodemographic data, menstrual pattern and dysmenorrhea in adolescents, Visual analog scale, Pittsburgh Sleep Quality Index, DSM-5 Level 2 Sleep Disorders Scale, Brief Symptom Inventory, and the Turgay Diagnostic and Statistical Manual of Mental Disorders, 4th edition-Based Child and Adolescent Disruptive Behavior Disorders Screening and Rating Scale were used to measure outcomes. Results: A hundred and four (49.8%) adolescents reported having pain that affects daily activities during menstruation. These adolescents had worse sleep quality, more inattention and hyperactivity-impulsivity problems, and other psychological symptoms of anxiety, depression, somatization, negative self-perception, and hostility in comparison to others (P < 0.05). The menstrual pain severity, measured by VAS, was positively correlated with ADHD symptoms and all other psychological parameters (P < 0.05). Conclusion: PD affecting daily-activities may be related to ADHD symptoms and psychiatric distress. Future studies are needed to support the association between ADHD and PD. Assessing the psychiatric problems of adolescents with dysmenorrhea is important.